Contribution of household dishwashing to microplastic pollution - Daniel Sol; Andrea Menéndez-Manjón; Sofía Carrasco; Jacinto Crisóstomo-Miranda; Amanda Laca; Adriana Laca; Mario Díaz (Environmental Science and Pollution Research, 2023)
At household level, clothes washing has been recognised as an emitter of microplastics (MPs) into the environment and it is supposed that dishwashing is also a source of MPs, although little attention has been paid so far. In this work, the emission of MPs released from dishwashing procedures at household level has been studied. The effect of different parameters such as time, temperature and type of detergent has been analysed. In addition, the MP content of tap water has been evaluated in order to determine its contribution to the MPs in dishwasher effluent. Results showed that when the dishwasher was operated empty with a pre-wash programme (15 min and room water temperature), between 207 and 427 MPs were released per load (3 L), whereas this value increased notably with an intensive programme (164 min and water at 70 °C) (1025–1370 MPs per load, 15 L), which highlighted the effect of temperature and time on MP release. Additionally, when a polypropylene lunch box was washed, the number of MPs released increased by 14 ± 3 MPs and 166 ± 12 MPs of total. Finally, the influence of the use of detergent with the dishwasher empty and containing lunch boxes has been studied. With detergent, 35–54% more MPs were released from dishwasher accessories, whereas no additional release took place from lunch boxes. This work shows for the first time the important contribution of domestic dishwashing to MP pollution and the environmental benefits of using more environmentally friendly materials in both dishwashing machine accessories and food utensils.